Exploring a New Cueing Device in People Who Experience Freezing of Gait: Acceptance of a Study Design - Agnes Wilhelm; Tanja Riedl; Christian Paumann; Jessie Janssen (Parkinson's Disease)
Background. Freezing of Gait (FoG) is a disabling symptom of Parkinson’s Disease (PD) and is defined as a “brief episodic absence or marked reduction of forward progression of the feet despite the intention to walk.” Compensatory strategies such as cueing and high frequency vibrotactile stimulation can reduce FoG severity and improve gait parameters. A new Sternal high frequency Vibrotactile Stimulation Device (SVSD) with cueing function has been developed, however the clinical effects of this device are yet to be fully investigated. Objective. The aim of this study was to investigate, if the proposed study design using a SVSD and gait analysis sensor insoles was acceptable for people with PD. Methods. This feasibility study was designed as a randomized cross-over study. Thirteen participants took part in a one off 60-minute data collection session. The acceptability of the study design was assessed with a mixed methods questionnaire considering each step of the study process. Secondary outcome measures were the feasibility of using the 10 Metre Walk Test (10MWT), the Freezing of Gait Score (FoG-Score), and Patient Global Impression of Change (PGI-C) with and without the SVSD. Results. The participants scored all aspects of the study design as very satisfactory. In addition, all participants could perform the secondary outcome measures and were deemed feasible. Feedback from open ended questions provided ideas and considerations for adaptations of future clinical studies. Conclusion. The proposed study design was acceptable for people with PD. Implications. This study design, with small adaptations, can be used for larger studies to evaluate the effect of an SVSD on FoG in people with PD.